Emerging therapies for autosomal dominant polycystic kidney disease with a focus on cAMP signaling - Zhou, Xia; Torres, Vicente E. (Frontiers in Molecular Biosciences, 2022)
Autosomal dominant polycystic kidney disease (ADPKD), with an estimated genetic prevalence between 1:400 and 1:1,000 individuals, is the third most common cause of end stage kidney disease after diabetes mellitus and hypertension. Over the last three decades there has been great progress in understanding its pathogenesis. This allows the stratification of therapeutic targets into four levels, gene mutation and polycystin disruption, proximal mechanisms directly caused by disruption of polycystin function, downstream regulatory and signaling pathways, and non-specific pathophysiologic processes shared by many other diseases. Dysfunction of the polycystins, encoded by the PKD genes, is closely associated with disruption of calcium and upregulation of cyclic AMP and protein kinase A (PKA) signaling, affecting most downstream regulatory, signaling, and pathophysiologic pathways altered in this disease. Interventions acting on G protein coupled receptors to inhibit of 3',5'-cyclic adenosine monophosphate (cAMP) production have been effective in preclinical trials and have led to the first approved treatment for ADPKD. However, completely blocking cAMP mediated PKA activation is not feasible and PKA activation independently from cAMP can also occur in ADPKD. Therefore, targeting the cAMP/PKA/CREB pathway beyond cAMP production makes sense. Redundancy of mechanisms, numerous positive and negative feedback loops, and possibly counteracting effects may limit the effectiveness of targeting downstream pathways. Nevertheless, interventions targeting important regulatory, signaling and pathophysiologic pathways downstream from cAMP/PKA activation may provide additive or synergistic value and build on a strategy that has already had success. The purpose of this manuscript is to review the role of cAMP and PKA signaling and their multiple downstream pathways as potential targets for emergent therapies for ADPKD.